A convenient approach of MIP/Co–TiO2 nanocomposites with highly enhanced photocatalytic activity and selectivity under visible light irradiation. Issue 73 (21st July 2016) - Liu, Yang; Zhu, Jielian; Liu, Xiang; Li, Hexing
Abstract : MIP/Co–TiO2 nanocomposites were synthesized. Their mechanisms of preferable photocatalytic activity and good selectivity for target contaminants were identified and discussed. Abstract : Molecular imprinted polymer coated Co-doped TiO2 nanocomposites (MIP/Co–TiO2 nanocomposites) were successfully synthesized by a surface molecular imprinting technique using rhodamine B (RhB) as the template molecule and p -phenylenediamine as the functional monomer. The surface structure and properties of the nanocomposite catalysts were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption/desorption measurements (BET) and UV-vis diffuse reflectance spectra (UV-vis DRS). The preferentially selected degradation and activity of imprinted photocatalysts were evaluated by degradation of the template molecule RhB relative to rhodamine 6G (Rh6G) under visible light irradiation. Compared with the non-imprinted Co-doped TiO2 nanocomposites (NIP/Co–TiO2 nanocomposites), the MIP/Co–TiO2 nanocomposites exhibited higher photo-degradation rate for RhB and also showed enhanced selective activity for RhB. The k value for the photodegradation of RhB over MIP/Co–TiO2 nanocomposites was 0.03606 min −1, being 215.7% that of RhB over NIP/Co–TiO2 nanocomposites (0.01672 min −1 ) and 337.3% that of RhB over Co–TiO2 nanoparticles (0.01069 min −1 ). The k value for the photodegradation of RhB over MIP/Co–TiO2 nanocomposites was 0.03606 min −1, being 150.5% that of Rh6G over MIP/Co–TiO2 nanocomposites (0.02396 min −1 ). Moreover, the MIP/Co–TiO2 nanocomposites exhibited high stability and reusability.